Periungual basal cell carcinoma: A case report with review of literature - Debabrata Bandyopadhyay; Sumit Sen (Wolters Kluwer Medknow Publications, 2011)
Basal cell carcinomas (BCCs) are considered to be uncommon around the nail plate. An indolent lesion of this region should arouse suspicion of potential malignancy and a skin biopsy should be undertaken without delay. Early diagnosis can enable the physician to render simpler nondestructive modalities of treatment. In this article, we describe such a case of longstanding BCC of this region mimicking a traumatic ulcer. The nature of the ailment was finally discovered on biopsy and the carcinoma was initially treated with topical Imiquimod.